Exploring the impact of tonal inventory on speech perception across languages: a study of MMN responses in tonal language speakers - Hsu, Chun-Hsien; Cheong, Tong-Hou; Huang, Wen-Jun (Frontiers in Psychology, 2024)
Previous research on the perception of segmental features of languages has established a correlation between the phoneme inventory of a language and its speakers' perceptual abilities, as indexed by discrimination tasks and Mismatch Negativity (MMN). Building on this background, the current study elucidated the relationship between perceptual ability and tonal inventory by utilizing two tonal languages. Two groups of participants were included in the present experiment: Mandarin speakers and Hakka-Mandarin speakers. Onset latency analysis revealed a significant difference in the Mandarin syllable condition, with Hakka-Mandarin speakers demonstrating earlier MMN latency than Mandarin speakers. This suggests a more efficient auditory processing mechanism in Hakka-Mandarin speakers. Both groups, however, showed similar MMN latency in the Hakka syllable condition. The interaction between language background and syllable type indicates that other factors, such as syllable sonority, also influence MMN responses. These findings highlight the importance of considering multiple phonemic inventories and syllable characteristics in studies of tonal perception.